2018
DOI: 10.1038/s41563-018-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface distortion as a unifying concept and descriptor in oxygen reduction reaction electrocatalysis

Abstract: Tuning the surface structure at the atomic level is of primary importance to simultaneously meet the electrocatalytic performance and stability criteria required for the development of low-temperature proton-exchange membrane fuel cells (PEMFCs). However, transposing the knowledge acquired on extended, model surfaces to practical nanomaterials remains highly challenging. Here, we propose 'surface distortion' as a novel structural descriptor, which is able to reconciliate and unify seemingly opposing notions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
344
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 396 publications
(358 citation statements)
references
References 52 publications
14
344
0
Order By: Relevance
“…[153][154][155] A recent work by Evan Ma [156] has used MD simulations to discuss the role of SRO and geometrically unfavorable motifs (GUMs) in amorphous alloys correlating the GUMs with the liquid-like regions in the observed plasticity for the alloys and highlighting the SRO as partially responsible for the thermodynamic and kinetic stability of the amorphous alloy. This point was recently confirmed for bimetallic alloys [132] and to track this surface and bulk transition in MGNs by means of computing chemistry (either by Stochastic methods or tracking trajectories via MD) would provide a unique perspective on the design of MGNs electrocatalysts. In fact the majority of MD studies on MGs have been focused on addressing structural issues either on thin-film [157] or bulk MGs [154] and there is literature deficit on computing chemistry applied to MGs or MGNs.…”
Section: Can Computational Modeling and Advances In Mgns Help On Unramentioning
confidence: 71%
See 2 more Smart Citations
“…[153][154][155] A recent work by Evan Ma [156] has used MD simulations to discuss the role of SRO and geometrically unfavorable motifs (GUMs) in amorphous alloys correlating the GUMs with the liquid-like regions in the observed plasticity for the alloys and highlighting the SRO as partially responsible for the thermodynamic and kinetic stability of the amorphous alloy. This point was recently confirmed for bimetallic alloys [132] and to track this surface and bulk transition in MGNs by means of computing chemistry (either by Stochastic methods or tracking trajectories via MD) would provide a unique perspective on the design of MGNs electrocatalysts. In fact the majority of MD studies on MGs have been focused on addressing structural issues either on thin-film [157] or bulk MGs [154] and there is literature deficit on computing chemistry applied to MGs or MGNs.…”
Section: Can Computational Modeling and Advances In Mgns Help On Unramentioning
confidence: 71%
“…All three aforementioned authors have reported higher specific activity for ORR than Pt/C. [132] Following this concept, activated or dealloyed quaternary MGs would possess a wide distribution of different catalytic sites with several at close to optimal ORR activity in a Sabatier diagram that dominates the kinetics. Nesselberger et al attributed this improvement due to lattice-strain effect that arises from the dealloying of bi-metallic materials, [129] as previously demonstrated by Nørskov and co-workers [130] and Strasser et al [131] Kolla and Smirnova elaborate that the measured improvements are proportional to the fcc lattice parameter which is consistent with previous studies.…”
Section: Orrmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that superior catalytic activity could be achieved by pinning the transition metal redox energies at the top of the O-2p band. [2,8] Nanostructure engineering by reducing the material's dimension and size is the most commonly deployed approach to increase the exposure of active sites. [27,[29][30][31][32][33][34][35] However, its catalytic activity still needs to be enhanced to meet the requirements of practical applications.…”
mentioning
confidence: 99%
“…[25][26][27][28] LiCoO 2 has recently been intensively explored as OER and ORR catalyst. [2,8] Nanostructure engineering by reducing the material's dimension and size is the most commonly deployed approach to increase the exposure of active sites. Toward the intelligent design of high performance electrocatalysts, two general strategies (enhancing the intrinsic activity and increasing the number of active sites) have been applied to improve the activity of targeted electrocatalysts.…”
mentioning
confidence: 99%